The Role of Glyceraldehyde-3-Phosphate Dehydrogenases in NADPH Supply in the Oleaginous Filamentous Fungus Mortierella alpina - Wang, Shunxian; Chen, Haiqin; Tang, Xin; Zhang, Hao; Hao, Guangfei; Chen, Wei; Chen, Yong Q. (Frontiers in Microbiology, 2020)
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a highly conserved enzyme within the glycolytic pathway. GAPDH catalyzes the transformation of glyceraldehyde 3-phosphate to glycerate-1, 3-biphosphate, a process accompanied by the production of NADH. Its role in the NADPH production system of the oleaginous filamentous fungus Mortierella alpina was explored. Two copies of genes encoding GAPDH were characterized, then endogenously overexpressed and silenced through Agrobacterium tumefaciens-mediated transformation methods. The results showed that the lipid content of the overexpression strain, MA-GAPDH1, increased by around 13 %. RNA interference of GAPDH1 and GAPDH2 (MA-RGAPDH1 and MA-RGAPDH2) greatly reduced the biomass of the fungus. The lipid content of MA-RGAPDH2 was found to be about 23% higher than that of the control. Both of the lipid-increasing transformants showed a higher NADPH/NADP ratio. Analysis of metabolite and enzyme expression levels revealed that the increased lipid content of MA-GAPDH1 was due to enhanced flux of glyceraldehyde-3-phosphate to glycerate-1, 3-biphosphate. MA-RGAPDH2 was found to strengthen the metabolic flux of dihydroxyacetone phosphate to glycerol-3-phosphate. Thus, GAPDH1 contributes to NADPH supply and lipid accumulation in M. alpina, and has a distinct role from GAPDH2.